Hubungan Sikap Mengajar Guru PAK dan Motivasi Belajar Siswa Kelas X SMA Negeri 1 Sipoholon Tahun Pembelajaran 2024/2025 - Putri Indah Sihotang; Oktober Tua Aritonang; Risden Anakampun; Elisamark Sitopu; Simion Harianja (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
This study aims to determine the strength of the positive and significant relationship between the teaching attitude of Christian Religious Education (PAK) teachers and the learning motivation of class X students at SMA Negeri 1 Sipoholon in the 2024/2025 academic year. This research uses a quantitative method with descriptive inferential statistical analysis. The population of the study consists of all class X students of SMA Negeri 1 Sipoholon in the 2024/2025 academic year, totaling 281 students. The sampling technique used is random sampling, selecting 25% of the population, which is 65 students. The research instrument used is a closed-ended questionnaire. The data analysis results show that: a) The calculated r value = 0.560 > the r table value = 0.244, indicating a positive relationship between variable X (the teaching attitude of PAK teachers) and variable Y (the students' learning motivation). b) Hypothesis testing showed that t count = 5.365 > t table = 1.980, so H0 is rejected and Ha is accepted. Based on these results, it can be concluded that there is a significant positive relationship between the teaching attitude of PAK teachers and the learning motivation of class X students at SMA Negeri 1 Sipoholon in the 2024/2025 academic year. These findings are expected to contribute to the improvement of the quality of learning in the school.